Implementasi Kebijakan Pemenuhan Hak Anak Desa Bojong dalam mewujudkan Desa Layak Anak di Kabupaten Pandeglang - Listyaningsih Listyaningsih; Ismanto Ismanto (Jurnal Administrasi Publik, 2021)
The high number of violence that occurred in Pandeglang Regency is not directly proportional to the increase in the achievement of the Pandeglang category as an Intermediate Level Child Friendly Regency. This study aims to describe how the implementation of the fulfillment of children's rights in Bojong Village, Pandeglang Regency. A quantitative approach is used to collect data and then analyze it. The population in this study are children aged 7-17 years, where they are citizens who are the targets of the Child Friendly Village policy. The theory used in this study is the theory of G. Edward III's Policy Implementation and also the Child Friendly Village indicator. The results of the study indicate that the rights of children in Bojong Village have not been fulfilled optimally because there are several indicators that are still worrying, including the fulfillment of civil rights that have not been optimal, the lack of facilities for child growth and development and the low protection of children from acts of violence. So that effective communication between stakeholders is needed, increasing apparatus resources and community participation in fulfilling children's rights in Bojong Village to realize Child Friendly Village.